2022
DOI: 10.1093/pnasnexus/pgac216
|View full text |Cite
|
Sign up to set email alerts
|

Associations between abstract working memory abilities and brain activity underlying long-term recognition of auditory sequences

Abstract: Memory is a complex cognitive process comprised by several subsystems, namely short- and long-term memory and working memory (WM). Previous research has shown that adequate interaction between subsystems is crucial for successful memory processes such as encoding, storage and manipulation of information. However, few studies have investigated the relationship between different subsystems at the behavioral and neural levels. Thus, here we assessed the relationship between individual WM abilities and brain activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 71 publications
(85 reference statements)
5
40
1
1
Order By: Relevance
“…Our results are coherent with the ones reported by Bonetti et al 4246 , which showed a large network of brain areas involved in the recognition of previously memorized auditory sequences. Specifically, they highlighted the crucial role of the auditory cortex, insula, hippocampus, cingulate gyrus, basal ganglia, frontal operculum, and orbitofrontal cortices.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are coherent with the ones reported by Bonetti et al 4246 , which showed a large network of brain areas involved in the recognition of previously memorized auditory sequences. Specifically, they highlighted the crucial role of the auditory cortex, insula, hippocampus, cingulate gyrus, basal ganglia, frontal operculum, and orbitofrontal cortices.…”
Section: Discussionsupporting
confidence: 93%
“…A relevant difference between Bonetti et al 43, 44 and Fernández Rubio et al 45, 46 and our findings is related to the frequency of the evoked responses. While these studies showed that the recognition of the temporal sequences was associated with activity in the cingulate, hippocampus, insula, and inferior temporal cortex in a very slow frequency (0.1 – 1 Hz) accompanying the whole duration of the sequences, here we observed a distinct, faster response to each tone of the sequence.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, we found specific effects of aging on STM capacity for rhythmic sequences, but not for melodic sequences, and on LTM ability for identifying new sequences, but not for recognizing old sequences. Following previous studies on the spatiotemporal dynamics of memory [66][67][68][69] , our future research will focus on correlating these differences in memory capacity to the patterns of brain activity and connectivity during short-term auditory memory recognition.…”
Section: Discussionmentioning
confidence: 99%